Predictors of cardiac rehabilitation attendance following primary percutaneous coronary intervention for ST‐elevation myocardial infarction in Australia. (8th February 2016) - Soo Hoo, Soon Yeng; Gallagher, Robyn; Elliott, Doug
Abstract: Cardiac rehabilitation is an important component of recovery and secondary prevention following urgent primary percutaneous coronary intervention. However, attendance and factors that predict participation by patients admitted with ST‐elevation myocardial infarction remain unclear. This Australian study was conducted using a descriptive, comparative design. Consecutive patients ( n = 246) at two hospitals were interviewed by telephone at four weeks and six months. Open‐ended questions were used to assess cardiac rehabilitation attendance, sociodemographics, modifiable risk factors, clinical outcomes, and post‐discharge health support. Post‐discharge home visits at four weeks (odds ratio: 2.64, 95% confidence interval: 1.48‐4.71) and at six months were associated with better cardiac rehabilitation attendance; more males participated at four weeks and at six months. The results suggest the need to integrate post‐discharge health support with cardiac rehabilitation to facilitate recovery after primary percutaneous coronary intervention, particularly for females with ST‐elevation myocardial infarction.